KEANEKARAGAMAN TUMBUHAN HERBA DI SUNGAI PAYETI SEBAGAI MEDIA PEMBELAJARAN BIOLOGI BERBENTUK HERBARIUM - Putri Ronauli Sihombing; Erfy Melany Lalupanda; Yoin Meissy Matulessy (Bioscientiae, 2024)
The purpose of this research is to know the diversity of plants and the use of plants as learning media in the form of a herbarium. This type of research is a descriptive ecological research with a quantitative approach. Based on the results of the research, it is known that the diversity of herbaceous plants in the Payeti River is classified as moderate with a value of H' = 2.703. Analysis of other ecological indices such as density is known to be the largest density by Digitaria setigera with a relative density value (KR) of 9.54% while the smallest density by Eleocharis geniculate which has a relative density value (KR) of 0.27%, the highest frequency is owned by Digitaria setigera which has a relative frequency value of 11.14% while Eleocharis geniculata has a low frequency species with a relative frequency value of 0.59% and a dominance index of herbaceous plants of 0.071 which is relatively low. The diversity of herbaceous plants was used as a learning medium in the form of a herbarium which obtained an average validation value of 95.06 and was classified as very valid.